Spatiotemporal Evolution Patterns and Influencing Factors of Rural Shrinkage Under Rapid Urbanization: A Case Study of Zhejiang Province, China - Rongrong Zhuo; Xinni Xu; Yuchen Zhou; Xinwei Guo (Land)
Under the context of urban–rural mobility driven by rapid urbanization, rural shrinkage is particularly pronounced in the developed regions of China, yet studies exploring its patterns and influencing factors are scarce. This paper uses Zhejiang Province as a case study to investigate the spatiotemporal evolution and influencing factors of rural shrinkage from 2000 to 2020. By employing spatial autocorrelation analysis and spatial econometric modeling, the study investigates both population and spatial shrinkage. The findings reveal the following: (1) a marked spatiotemporal imbalance exists in population and spatial dynamics in Zhejiang’s rural areas, where the interplay between population and spatial shrinkage contributes to regional disparities. (2) From 2000 to 2020, population shrinkage shifted from a global shrinkage to a more localized decline in the northeast and southwest, while spatial shrinkage shifted from a global non-shrinkage to a focus on central and southwestern areas. (3) Urbanization significantly negatively impacts rural shrinkage, while the spatial spillover effect of urbanization is notably positive. In contrast, factors related to natural conditions, location, and agricultural investment show significant positive effects but also notable negative spatial spillover effects. This study aims to provide a comprehensive analytical framework for understanding rural shrinkage and offers valuable insights for rural development, infrastructure planning, and spatial governance.